AN ANALYSIS OF INDONESIAN MILKFISH UPSTREAM SUPPLY CHAIN: SYSTEM DYNAMICS APPROACH - Eunike, Agustina; Sugiono, Sugiono; Tama, Ishardita Pambudi; Widiyawati, Sri; Pramono, Galih D.A; Yuniarti, Rahmi (JEMIS (Journal of Engineering & Management in Industrial System), 2021)
Milkfish is common aquaculture product consumed by Indonesian people. However, the ponds of milkfish in Indonesia manage by Small Medium Enterprises scale of farmers which have problems in sustaining the business. This study proposes supply chain analysis in the upstream level to develop strategic to improve the profit of milkfish farmers. Milkfish supply chain is a network of many actors that work together to create and deliver milkfish and its culinary products to the end-user. This paper defines the partnership strategies between the farmers and suppliers as well as the support from government as facilitator and regulator. Moreover, system dynamic approach analyses the scenarios of partnership to outline the benefit obtain by the milkfish supply chain. Finally, the simulation results recommend the partnership to fertilizer supplier will give significant increase in profit of the milkfish farmers.